Association of Urinary Bisphenol A concentration with medical disorders and laboratory abnormalities in adults - Lang, I.; Galloway, T.; Scarlett, Alan; Henley, W.; Depledge, M.; Wallace, R.; Melzer, D. (2008)
Context: Bisphenol A (BPA) is widely used in epoxy resins lining food and beverage containers. Evidence of effects in animals has generated concern over low-level chronic exposures in humans. Objective: To examine associations between urinary BPA concentrations and adult health status. Design, Setting, and Participants: Cross-sectional analysis of BPA concentrations and health status in the general adult population of the United States, using data from the National Health and Nutrition Examination Survey 2003-2004. Participants were 1455 adults aged 18 through 74 years with measured urinary BPA and urine creatinine concentrations. Regression models were adjusted for age, sex, race/ ethnicity, education, income, smoking, body mass index, waist circumference, and urinary creatinine concentration. The sample provided 80% power to detect unadjusted odds ratios (ORs) of 1.4 for diagnoses of 5% prevalence per 1-SD change in BPA concentration, or standardized regression coefficients of 0.075 for liver enzyme concentrations, at a significance level of P<.05. Main Outcome Measures: Chronic disease diagnoses plus blood markers of liver function, glucose homeostasis, inflammation, and lipid changes. Results: Higher urinary BPA concentrations were associated with cardiovascular diagnoses in age-, sex-, and fully adjusted models (OR per 1-SD increase in BPA concentration, 1.39; 95% confidence interval [CI], 1.18-1.63; P=.001 with full adjustment). Higher BPA concentrations were also associated with diabetes (OR per 1-SD increase in BPA concentration, 1.39; 95% confidence interval [CI], 1.21-1.60; P<.001) but not with other studied common diseases. In addition, higher BPA concentrations were associated with clinically abnormal concentrations of the liver enzymes ?-glutamyltransferase (OR per 1-SD increase in BPA concentration, 1.29;95%CI, 1.14-1.46; P<.001) and alkaline phosphatase (OR per 1-SD increase in BPA concentration, 1.48; 95% CI, 1.18-1.85; P=.002). Conclusion: Higher BPA exposure, reflected in higher urinary concentrations of BPA, may be associated with avoidable morbidity in the community-dwelling adult population. ©2008 American Medical Association. All rights reserved.